Checklist and identification key for clingfishes (Actinopterygii: Gobiesocidae) from the Mediterranean Sea - Kovačić, Marcelo; Tiralongo, Francesco; Wagner, Maximilian (Zootaxa, 2026)
We provide a comprehensive checklist and identification key of the 13 known species of clingfishes (Actinopterygii: Gobiesocidae) occurring in the Mediterranean Sea, including five species described within the last decade. The species included in this checklist are confirmed based on rigorous evidence-based records. To date, all clingfishes in the Mediterranean are native and no alien species have been recorded.